Surveillance in Trump’s America - Monahan, Torin (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
This paper sketches some of the key dangers presented by the second Trump presidency. We are witnessing a mainstreaming of far-right positions with profound implications both for government and the constitution of society. This moment is marked by censorship and self-censorship of the media, surveillance and punishment of immigrant communities, attacks on higher education, throttled scientific research, a war on gender, the evisceration of government agencies, reduced checks on disinformation or hate speech, and threats to international security. The Trump model of governance builds on hate to breed instability and chaos. These are the dynamics we must confront and disarm.